2015
DOI: 10.1111/jth.12836
|View full text |Cite
|
Sign up to set email alerts
|

Use of next‐generation sequencing and candidate gene analysis to identify underlying defects in patients with inherited platelet function disorders

Abstract: SummaryBackgroundInherited platelet function disorders (PFDs) are heterogeneous, and identification of the underlying genetic defects is difficult when based solely on phenotypic and clinical features of the patient.ObjectiveTo analyze 329 genes regulating platelet function, number, and size in order to identify candidate gene defects in patients with PFDs.Patients/methodsTargeted analysis of candidate PFD genes was undertaken after next‐generation sequencing of exomic DNA from 18 unrelated index cases with PF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 29 publications
(41 reference statements)
0
49
0
2
Order By: Relevance
“…73,85 The greatest diagnostic success for d-SPD has been in the multisystem syndromes such as Chediak Higashi syndrome and HPS, but most patients with nonsyndromic d-SPD remain undiagnosed. 86 In ongoing large-scale HTS projects such as Genotyping and Phenotyping of Platelets 87,88 and BRIDGE-BPD, 2,22,48 the lack of gene discovery for d-SPD, even in these large patient cohorts, highlights a need to analyze the noncoding regulatory regions of the genome via whole genome sequencing (WGS) while also exploring novel methods of data analysis and integration. We discuss such methods in more detail in the final section.…”
Section: Ipd Gene Discovery To Datementioning
confidence: 99%
“…73,85 The greatest diagnostic success for d-SPD has been in the multisystem syndromes such as Chediak Higashi syndrome and HPS, but most patients with nonsyndromic d-SPD remain undiagnosed. 86 In ongoing large-scale HTS projects such as Genotyping and Phenotyping of Platelets 87,88 and BRIDGE-BPD, 2,22,48 the lack of gene discovery for d-SPD, even in these large patient cohorts, highlights a need to analyze the noncoding regulatory regions of the genome via whole genome sequencing (WGS) while also exploring novel methods of data analysis and integration. We discuss such methods in more detail in the final section.…”
Section: Ipd Gene Discovery To Datementioning
confidence: 99%
“…WES and bioinformatics analysis were performed as described previously 8,15,16 ( Figure 1). The pathogenicity of variants was determined and called using the consensus guidelines as set out by the American College of Medical Genetics and Genomics and the Association for Molecular Pathology (ACMG guidelines).…”
Section: Whole Exome Sequencingmentioning
confidence: 99%
“…In addition, NGS studies, as applied to platelet function, provided significant results indicating that potentially damaging variants in platelet genes have low individual frequencies, but are collectively abundant among the population (45). Another previous study reported that potentially damaging variants are present in pedigrees with inherited platelet function disorders and may contribute to complex laboratory phenotypes (46). The genetic variants involved in the function of ALOX5 and ALOX5AP were described previously with mixed results regarding their involvement in the regulation of LT metabolism or vascularity, including platelet functions (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 98%